A Case of Metronidazole‐Induced Encephalopathy: Can Encephalopathy be Distinguished From Delirium Like Symptoms? - Maho Tanaka; Yasushi Kojima; Takahiro Nishimura; Satoshi Numazawa; Kenji Momo (Clinical Case Reports)
ABSTRACT Although the treatment strategies differ significantly, metronidazole‐induced encephalopathy and delirium manifest with similar clinical symptoms. Therefore, the potential risk of encephalopathy should be considered when treating patients with delirium.